2015
DOI: 10.1158/0008-5472.can-14-3380
|View full text |Cite
|
Sign up to set email alerts
|

EGF Receptor Promotes Prostate Cancer Bone Metastasis by Downregulating miR-1 and Activating TWIST1

Abstract: Dysregulation of the EGFR signaling axis enhances bone metastases in many solid cancers. However, the relevant downstream effector signals in this axis are unclear. miR-1 was recently shown to function as a tumor suppressor in prostate cancer cells, where its expression correlated with reduced metastatic potential. In this study, we demonstrated a role for EGFR translocation in regulating transcription of miR-1-1, which directly targets expression of TWIST1. Consistent with these findings, we observed decrease… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 36 publications
3
96
0
Order By: Relevance
“…miR‐1 has been reported to function as a tumour suppressor in a series of cancers (Chang et al . ). Overexpression of miR‐1 inhibited cancer cell proliferation and metastasis (Xiao et al .…”
Section: Discussionmentioning
confidence: 97%
“…miR‐1 has been reported to function as a tumour suppressor in a series of cancers (Chang et al . ). Overexpression of miR‐1 inhibited cancer cell proliferation and metastasis (Xiao et al .…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that miR-1 plays a role as a tumor suppressor gene in prostate [13], liver [14], and lung [15]. In thyroid cancer, miR-1 is significantly downregulated and displays the anti-tumor effect via targeting CCND2, CXCR4, and SDF-1alpha [16].…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNAs have been documented to directly inhibit TWIST1, including miR-1-1 [26], miR-33a [27, 28], miR-137 [29], miR-186 [30], miR-300 [31], miR-520d-5p [32], miR-539 [31], miR-543 [31], miR-675 [33], and miR-720 [34]. Most of these miRNAs repressed cancer cell EMT and metastasis in most examined cancer types, and some of them (miR-33a and miR-186) modulated cancer cell sensitivity to cisplatin by down-regulating TWIST1 [27, 30].…”
Section: Discussionmentioning
confidence: 99%